2022
DOI: 10.1371/journal.pone.0270260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the social relationships and mental health of older adults living alone: A two-year prospective cohort study

Abstract: Background Owing to the COVID-19 outbreak, older adults living alone, who can only connect socially outside their homes, are at risk of social isolation and poor mental health. This study aimed to identify the changes, before and after COVID-19, by sex and age, in social relationships (social activity, social network, and social support) and mental health (depression and suicide ideation) among older adults living alone. Methods This is a prospective cohort study of community-dwelling older adults who were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This result may have been affected by COVID-19, which began in 2019 [30,37]. Other studies similarly reported that the social activities of older adults decreased after COVID-19, with those of women decreasing more than those of men [35]. When analyzed by age group, the number of people met decreased more in the young-old group.…”
Section: Discussionmentioning
confidence: 91%
“…This result may have been affected by COVID-19, which began in 2019 [30,37]. Other studies similarly reported that the social activities of older adults decreased after COVID-19, with those of women decreasing more than those of men [35]. When analyzed by age group, the number of people met decreased more in the young-old group.…”
Section: Discussionmentioning
confidence: 91%
“…Increased social support in health behaviors was another positive impact of the corona during the COVID-19 pandemic compared to the pre-pandemic period in Tehran. Studies in other countries indicated increased family support during lockdown (Machón Sobrado et al, 2021) or increased social support levels in the third wave compared to the first wave of coronavirus (Ryu et al, 2022). Social support serves as a direct factor and a buffer against the negative impacts of COVID-19 stressors (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of the COVID-19 pandemic, limiting measures have been implemented to slow the spread of the virus, such as social distancing, wearing a face mask, home quarantine, and travel restrictions (Foong et al, 2022). Because older adults encountered greater mortality risks, and more severe illness and complications from viral infection than younger adults (Ryu et al, 2022), they were encouraged to avoid discretionary social activities and interactions, including those with family members (Foong et al, 2022). The resulting dramatic decline in social interactions has led to an elevated risk of social isolation, loneliness, depression, and anxiety among older adults (Polenick et al, 2021).…”
Section: Introductionmentioning
confidence: 99%